Determining Moral Value in Movies: An Analysis of the Movie “Onward” - Ayuni, Putri Qurota (Journal of Linguistics and Social Sciences, 2023)
Recent trends indicate a discernible decrease in the perceived significance of education, particularly among the adolescent and student demographic. The observed phenomenon can be attributed to a potential lack of parental emphasis on cultivating educational values in their offspring during early developmental stages, particularly in the contemporary era. The acquisition of knowledge through the guidance of teachers primarily centers on the assimilation of academic content, with limited attention given to examining potential moral decline among educators. The mitigation of this issue necessitates the active involvement of educators. Educators necessitate a medium that possesses the capacity to facilitate the instruction of various subjects, all the while ensuring that it imparts educational worth to the students. One of the forms of media that has gained significant popularity and cultural influence is the medium of film, commonly referred to as movies. The present study aims to explore and analyze the moral value embedded within the animated film titled "Onward." The data collection methods employed by the researcher encompassed both descriptive and qualitative approaches. The present study encompasses a three-step data analysis process: data condensation, data display, and conclusions verification. The researcher ultimately employed investigator triangulation to corroborate and substantiate the findings derived from the comprehensive analysis of the collected data. The research subject under investigation pertains to a cinematic production titled "Onward," which Dan Scanlan and C.S. Anderson co-directed. The researcher has identified various moral values depicted in the movie, including honesty, bravery, self-confidence, unselfishness, respect, love, and kindness. Through the examination and analysis of moral values, it is anticipated that cultivating virtuous qualities will contribute to developing a commendable character in a child. This process entails consistent endeavor, perseverance towards attaining personal goals, and unwavering affection and devotion towards one's familial unit.